2008
DOI: 10.1007/s10745-008-9207-0
|View full text |Cite
|
Sign up to set email alerts
|

International Labor Migration from a Tropical Development Frontier: Globalizing Households and an Incipient Forest Transition

Abstract: This study documents labor migration and its impacts on household income, material well-being, and land-use practices in Mexico's southern Yucatán and examines the relation of labor migration to local forest recovery. Drawing on a 203-household survey in 14 communities, we contrast migrating and non-migrating households, showing that migration earnings substitute for agricultural earnings and that migrating households cultivate significantly less farmland. A larger percentage of migrating households maintain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 51 publications
2
75
0
Order By: Relevance
“…Gender dynamics are critical to these trends, since in many cases women become the main farm managers, and this "feminization" of resource use exerts a major influence on the specifics of agricultural change (e.g., crop choice) and general outcomes (e.g., intensification or disintensification) [14,48,51,89,90,97,[172][173][174][175][176][177][196][197][198]. For example, the decline of chili pepper markets led to disintensification in the southern Yucatán region of Mexico through processes of livelihood diversification based on international migration and the influence of women's role in subsequent resource use [173,196,197]. In other cases, where women have migrated significantly, such as the case of remote-rural regions of Spain and elsewhere in Europe, including the former German Democratic Republic [99,198], new arrangements combine the "masculinization" of continued land use with social innovations in women's continued albeit reduced involvement.…”
Section: Results: Livelihood Diversification and Environmental Linkagesmentioning
confidence: 99%
“…Gender dynamics are critical to these trends, since in many cases women become the main farm managers, and this "feminization" of resource use exerts a major influence on the specifics of agricultural change (e.g., crop choice) and general outcomes (e.g., intensification or disintensification) [14,48,51,89,90,97,[172][173][174][175][176][177][196][197][198]. For example, the decline of chili pepper markets led to disintensification in the southern Yucatán region of Mexico through processes of livelihood diversification based on international migration and the influence of women's role in subsequent resource use [173,196,197]. In other cases, where women have migrated significantly, such as the case of remote-rural regions of Spain and elsewhere in Europe, including the former German Democratic Republic [99,198], new arrangements combine the "masculinization" of continued land use with social innovations in women's continued albeit reduced involvement.…”
Section: Results: Livelihood Diversification and Environmental Linkagesmentioning
confidence: 99%
“…Oxkutzcab was the only place that was experiencing any in-migration, but none of it was related to agriculture. Out-migration was also linked to a reduction in area under cultivation in the Calakmul region (Busch & Geoghegan 2010, Radel, et al 2010, Schmook & Radel 2008. The 2000 census data showed that the service sector is the most important source of employment in Oxkutzcab whereas agriculture continued to provide the main source of livelihood for people in Peto and especially Tzucacab.…”
Section: Discussionmentioning
confidence: 99%
“…For example based on survey data from 1986-1997, Programa de Apoyos Directos al Campo (PRO-CAMPO), an agricultural program implemented in 1994 with the goal of integrating agricultural markets and intensifying production, revealed only modest increases in market production, but an increase in deforestation occurred through the conversion of land to commercial chili production and pastures (Klepeis & Vance 2003). A study based on household surveys carried out in 1997 and 2003 found that similar land use choices were being made by some, although others were choosing to withdraw from agriculture all together and those who converted their land to pasture or commercial agriculture were using less land than previously devoted to extensive agricultural practices, resulting in a decrease in deforestation (Busch & Geoghegan 2010, Radel et al 2010, Schmook & Radel 2008. The increase in global environmentalism over the last 25 years has also led to the development of community-based conservation programs in the region, such as the Parks in Peril program and Empleo Temporal, which along with the enforcement of rules associated with the reserve seem to be contributing to a decline in deforestation (Rueda 2010).…”
Section: Land Use/land Cover Change and Associated Drivers In The Yucmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis ignores the possibility that labour could be substituted by household members, sharecroppers, hired workers, or mechanization (Hein 2006), or by turning to less labour-intensive, but more land-intensive agricultural activities, e.g. cattle ranching (Schmook and Radel 2008). The empirical literature shows that migration can result in deforestation or reforestation in the areas of origin of migrants, depending on the investments made by households, markets, policies, and institutions (Conway and Lorah 1995;Hecht et al 2006;Holder and Chase 2011;Kull et al 2007;Moran-Taylor and Taylor 2010;Naylor et al 2002;Taylor et al 2006).…”
Section: Migration Remittances and The Environment: The Approach Ofmentioning
confidence: 99%